2005
DOI: 10.1002/hep.20801
|View full text |Cite
|
Sign up to set email alerts
|

APOBEC‐mediated interference with hepadnavirus production†

Abstract: APOBEC3G is a cellular cytidine deaminase displaying broad antiretroviral activity. Recently, it was shown that APOBEC3G can also suppress hepatitis B virus (HBV) production in human hepatoma cells. In the present study, we characterized the mechanisms of APO-BEC-mediated antiviral activity against HBV and related hepadnaviruses. We show that human APOBEC3G blocks HBV production in mammalian and nonmammalian cells and is active against duck HBV as well. Early steps of viral morphogenesis, including RNA and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
115
1
2

Year Published

2006
2006
2009
2009

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 131 publications
(125 citation statements)
references
References 42 publications
7
115
1
2
Order By: Relevance
“…[30][31][32][33] Inhibition of pregenomic HBV RNA packaging by A3G was originally proposed by Turelli et al 30 as the mode of action. This is in line with a recent investigation by Rösler et al, 33 who reported an increased nuclease sensitivity of core-protein associated full-length pregenomic HBV RNA on expression of A3G. The extent of hypermutations in replicating HBV DNA induced by APOBEC3 editing enzymes is another matter of debate.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[30][31][32][33] Inhibition of pregenomic HBV RNA packaging by A3G was originally proposed by Turelli et al 30 as the mode of action. This is in line with a recent investigation by Rösler et al, 33 who reported an increased nuclease sensitivity of core-protein associated full-length pregenomic HBV RNA on expression of A3G. The extent of hypermutations in replicating HBV DNA induced by APOBEC3 editing enzymes is another matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…20,42,43 Our study confirms the expression of A3G and A3F in normal human liver and proves the hepatic expression of A3B mRNA. Thus, the concluding statement of Rösler et al 33 that a role of APOBEC3 cytidine deaminases in the HBV life cycle is speculative because expression of cytidine deaminases in untransformed liver has not been shown has to be amended. All four cytidine deaminases expressed in normal human liver are up-regulated in primary hepatocytes on IFN-␣ stimulation, and A3B, A3F and A3G achieve at least moderate mRNA expression levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations